Uwagi o Owidiuszu i złotym wieku Augusta - Łukaszewicz, Adam (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Publius Ovidius Naso was an outstanding poet of the Augustan age who after a period of successful activity was suddenly sent to exile without a formal judicial procedure. Ovid wrote frivolous poems but inserted into his works also the obligatory praises of Augustus. The standard explanation of his relegation to Tomis is the licentious content of his Ars Amatoria, which were believed to offend the moral principles of Augustus. However, the Ars had been published several years before the exile. The poet himself in his Pontic writings mentions an unspecified error and a carmen, pointing also to the Ars, without, however, a clear explanation of the reason for his fall. The writer of the present contribution assumes that the actual reason for the relegation of the poet without a trial were the verses of his Metamorphoses and especially the passage about the wicked stepmothers preparing poison. That could offend Livia who, according to gossip, used poison to get rid of unwanted family members. Ovid was exiled, but the matter was too delicate for a public justification of the banishment. When writing ex Ponto the poet could not explicitly refer to the actual cause of his exile.